Pengaruh Ekstrak Buah Pepino (Solanum muricatum Ait.) Terhadap Penurunan Kadar Kolesterol Mencit (Mus musculus L.) yang Diinduksi Diet Hiperkolesterol - Cut Putri Maghfirah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
The objective of this present study was to determine  the effect of  aqueous extract of Pepino fruit (Solanum muricatum Ait.) for decreasing the cholesterol blood of mice after induced by hypercholesterolemia diet.  Male moose were grouping into seven groups. The first group was a normal. The second group was a hypercholesterolemia. The third group was induced hypercholesterolemia diet and treatment with pepino extract in 420 mg doses. The forth group was induced hypercholesterolemia diet and treatment with pepino extract in 520 mg doses. The fifth group was induced hypercholesterolemia diet  and treatment with pepino extract in 640 mg doses. The sixth group was induces hypercholesterolemia diet and treatment with pepino extract in 1000 mg doses. The seven group was treatment by using atorvastatin drug. The ANOVA showed that the fifth group which treatment by pepino extract in 640 mg doses give a the most effective significant result of decreasing blood cholesterol compared with other doses. It is concluded that the pepino extract successfully decreasing the blood cholesterol of mice which induced by hypercholesterolemia diet.